2018
DOI: 10.1002/ajb2.1047
|View full text |Cite|
|
Sign up to set email alerts
|

Phylotranscriptomic analysis and genome evolution of the Cypripedioideae (Orchidaceae)

Abstract: Although WGD has played a role in the evolution of Orchidaceae, polyploidy does not appear to be responsible for the large genome size of slipper orchids. The conserved set of 775 largely single-copy nuclear genes identified in this study should prove useful in future studies of orchid evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 84 publications
2
34
0
Order By: Relevance
“…(the dataset lacked representatives of the genera Selenipedium and Mexipedium ). For purposes of comparison, we also found mycorrhizal information for four species of the subfamily Apostasioideae, which we used as an outgroup (Li et al, ; Unruh et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(the dataset lacked representatives of the genera Selenipedium and Mexipedium ). For purposes of comparison, we also found mycorrhizal information for four species of the subfamily Apostasioideae, which we used as an outgroup (Li et al, ; Unruh et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although species in the Cypripedioideae are represented in the Open Tree of Life, species were not resolved within genera at the time of writing. Instead, we used the general phylogeny of the Orchidaceae and of genera in the Cypripedioideae presented in Unruh et al () as a backbone. Onto this we added the phylogeny of genus Cypripedium developed in Li et al (), and phylogenies that we developed of sampled Paphiopedilum species and Apostasioideae species.…”
Section: Methodsmentioning
confidence: 99%
“…The evolutionary direction of the life forms of orchids can be roughly outlined from terrestrial to epiphytic, while saprophytic species independently evolved several times ( Sosa et al, 2016 ). Recent plastome analysis of orchid species has focused on comparisons with partially and fully mycoheterotrophic species ( Feng et al, 2016 ; Barrett & Kennedy, 2018 ; Unruh et al, 2018 ; Yuan et al, 2018 ). The molecular information on these species is of interest not only for the study of phylogenetics but also for evolutionary studies and species conservation.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-seq can be used to identify exon-exon splice junctions and different splicing patterns from different samples (Wilks et al 2018). In the slipper orchids (Cypripedioideae), results derived from RNA-seq data analysis showed the identification of mechanisms associated with genome evolution and transcriptomic data that were used to identify low-copy orthologous genes demonstrated that 775 single-copy nuclear genes should be valuable in future investigations of orchid evolution (Unruh et al 2018).…”
Section: Slipper Orchidsmentioning
confidence: 99%